2015
DOI: 10.1136/bcr-2015-212685
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterisation of two cancers of unknown primary cases supports a kidney cancer origin

Abstract: Cancer of unknown primary (CUP) comprises of 3–5% of new cancer diagnoses in the USA. Diagnostic work up typically includes CT of the chest, abdomen and pelvis, and histopathological review of tissue specimens. These measures are neither sensitive nor specific in determining tissue of origin (ToO) of primary tumours and, therefore, are unable to guide therapy. We present two cases of CUP for which we utilised ultra-deep genomic sequencing to identify the candidate ToO and to propose treatment. Patient 1 presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 12 publications
0
14
0
3
Order By: Relevance
“…However, presenting with mRCC with an undetectable primary is infrequent. A total of 12 cases were documented based on our literature review [5][6][7][8][9][10][11][12]; none of which had diffuse lymphadenopathy metastasizing from an unidentifiable renal primary as presented in our case. In such a challenging situation, immunohistochemical profiling as well as the promising field of molecular genetics aid in reaching a diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, presenting with mRCC with an undetectable primary is infrequent. A total of 12 cases were documented based on our literature review [5][6][7][8][9][10][11][12]; none of which had diffuse lymphadenopathy metastasizing from an unidentifiable renal primary as presented in our case. In such a challenging situation, immunohistochemical profiling as well as the promising field of molecular genetics aid in reaching a diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Upon reviewing the literature, a total of 12 cases of metastatic kidney cancer had no evidence of a renal mass [5][6][7][8][9][10][11][12]. In this case report, a case of mRCC with an initial presentation of generalized lymphadenopathy with an undetectable primary will be presented.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer of unknown primary origin (CUP) comprises 3-5% of new cancer diagnoses in the United States [118], and presents extreme therapeutic challenges. Genomics profiling of two CUP patients whose metastatic tumors showed clear cell histology favoring renal origin by Wei et al showed 3p loss, PBRM1 mutation, and SETD2 mutation in one patient, and NF2 mutation, SETD2 mutation, and TSC1 mutation in the other patient [119]. As the genomic and histologic features of these two CUP patients were consistent with cancer of unknown primary RCC (cupRCC) and because RCC is known to be refractory to conventional chemotherapy, both patients received front-line treatment with standard-of-care targeted therapies for RCC instead of chemotherapy for CUP, and derived clinical benefits [119].…”
Section: Cancer Of Unknown Primary Rccmentioning
confidence: 99%
“…The diagnostic utility of NGS can be seen in cases with diagnostic ambiguity and will grow as more unique genomic signatures are identified for each histology. For example, in a series of two patients with metastatic carcinoma of unknown primary, identification of SETD2 and NF2 mutations and heterozygous loss of chromosome 3p led to a diagnosis of renal cell carcinoma and treatment with mammalian target of rapamycin inhibitors in both cases .…”
Section: Functional and Clinical Significance Of The Specific Mutatiomentioning
confidence: 99%